Mixed Carbonates as Useful Substrates for a Fluorogenic Assay for Lipases and Esterases. Issue 4 (3rd February 2015) - Zadlo, Anna; Koszelewski, Dominik; Borys, Filip; Ostaszewski, Ryszard
Abstract Mixed carbonates of 7‐hydroxy‐4‐methylcoumarin were shown to be a new class of probe for fluorogenic assays. They are promising substrates for fingerprinting enzyme hydrolytic activity, and proved particularly useful because of the low level of nonspecific degradation and ease of synthesis. They are highly relevant for screening lipase and esterase libraries. These advantages make umbelliferyl carbonates highly suitable substrates for high‐throughput screening. Moreover, we report the use of chiral fluorogenic carbonates as enantiopreference probes.